Laser-Doppler vibrometer microscope with variable heterodyne carrier. (December 2018) - Kowarsch, Robert; Te, Rigele; Rembe, Christian
Abstract: The generation of a heterodyne carrier frequency for coherent detection via offset-locking in an optical phase-locked loop was demonstrated in communication, spectroscopy and other fields. In state-of-the-art laser-Doppler vibrometers (LDV), common acoustooptic devices (Bragg cells) allow efficient heterodyning with a static frequency. Moving mechanical parts vibrate in many technical applications, e.g. moving cars, trains, robots, ect.. In such applications, a large laser-Doppler-shift generated by the movement impairs the measurement of the relevant vibrations. A variation of the frequency offset of the interfering laser beams can suppress the Doppler effect of high-speed movements with slow speed variations and adjusts the signal spectrum to the optimal value. Thus, the electronic bandwidth can be set to an optimal value within the modulation bandwidth of the relevant vibrations. However, Bragg cells are not well applicable to shift laser frequencies without affecting the interferometer adjustment. In this paper, we propose offset locking of two independent lasers with an optical phase-locked loop to exploit the possibility of flexible heterodyne-carrier generation for laser-Doppler vibrometry. We demonstrate a LDV setup with offset locked visible DBR semiconductor lasers for a flexible heterodyning up to 200MHz and present first measurements.